A surface treatment method for aluminum alloy
Through pickling, roughening treatment and anodizing treatment, combined with specific additives, the surface roughness of the aluminum alloy and the density of the oxide film are improved, the problem of insufficient corrosion resistance of the aluminum alloy is solved, and its corrosion resistance is significantly enhanced.
Patent Information
- Application Number
- CN202411019604.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-07-29
AI Technical Summary
Aluminum alloys are prone to corrosion in harsh environments and have insufficient corrosion resistance.
A surface treatment method of an aluminum alloy is adopted, including pickling, roughening and anodizing treatment. To the crude liquid, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added, and to the anodized electrolyte, titanium dioxide-silia composite sol and silica-POSS composite were added.
By increasing the surface roughness and forming a dense corrosion-resistant oxide film, the corrosion resistance of aluminum alloy is significantly improved.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to a surface treatment method for an aluminum alloy. Background Art
[0002] Aluminum alloy has excellent mechanical properties, light weight, and is easy to process and shape. It can be manufactured into parts and components of complex shapes through various processing methods such as casting, forging, die-casting, extrusion, etc. It has been widely used in aerospace, automotive industry, electronic products, and construction. The roughening process of the aluminum alloy surface is an important surface treatment method. By increasing the surface roughness, the bonding force between the aluminum alloy and other materials is enhanced, ensuring that the components are not prone to peeling or falling off during use, thereby improving the durability of the aluminum alloy. However, the roughened aluminum alloy is prone to corrosion in harsh environments, and the corrosion resistance of the aluminum alloy needs to be improved.
[0003] In order to solve the above problems and improve the corrosion resistance of aluminum alloy, the present invention provides a surface treatment method of aluminum alloy. Summary of the invention
[0004] The object of the present invention is to provide a surface treatment method for aluminum alloy to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A surface treatment method for an aluminum alloy comprises the following steps:
[0007] Step 1: Take the aluminum alloy, pickle it with dilute sulfuric acid for 3-4 seconds, wash it with water, and dry it;
[0008] Step 2: roughening the cleaned aluminum alloy with a roughening liquid for 15-20 minutes at a temperature of 60-62° C., cleaning, drying, and then anodizing to obtain a treated aluminum alloy;
[0009] The electrolyte used for anodization is: 100 mL of deionized water as a solvent, wherein: 0.1-0.15 g of silica-POSS composite, 1-1.3 g of titanium dioxide-silicon dioxide composite sol, 1.2-1.5 g of sulfuric acid, and 5-6 g of disodium ethylenediaminetetraacetate.
[0010] More optimally, the preparation method of the silica-POSS complex is: take amino POSS, multi-shell silica particles, and toluene, stir evenly, add Tris buffer with a pH value of 7.5, react at 80-85°C for 6-7h, cool, remove the supernatant, centrifuge, precipitate, and dry to obtain the silica-POSS complex.
[0011] More optimally, the preparation method of the multi-shell silica particles is: take propanol and deionized water, stir evenly, add sodium hydroxide aqueous solution, add tetraethyl orthosilicate at 25-30°C, stir for 3-4h at 25-30°C, add sodium hydroxide aqueous solution, stir for 3-4h, add sodium hydroxide aqueous solution again, stir for 3-4h, centrifuge, wash, and dry to obtain multi-shell silica particles.
[0012] More optimally, the preparation method of the amino POSS is: take acetonitrile, tetraethylammonium hydroxide, propanol, and deionized water, stir evenly, add γ-aminopropyltriethoxysilane dropwise and stir for 15-20 minutes, heat to 55-65°C, stir for 22-26 hours, cool to 25-30°C, then add it to tetrahydrofuran at 0°C, precipitate, filter, and dry to obtain the amino POSS.
[0013] More optimally, the preparation method of the titanium dioxide-silicon dioxide composite sol is: take ethyl orthosilicate, methanol, hydrochloric acid, and deionized water, stir for 1-2 hours at 25-30°C to obtain a silica sol; take benzoyl acetone and methanol, stir for 30-40 minutes at 25-30°C to obtain a benzoyl acetone solution, add tetrabutyl titanate and acrylic acid, and continue stirring for 2-3 hours to obtain a titanium dioxide sol; take the silica sol and the titanium dioxide sol, stir evenly, let stand and age for 22-26 hours to obtain a titanium dioxide-silicon dioxide composite sol.
[0014] More optimally, the roughening liquid is: 1000 mL of deionized water as a solvent, including 120-125 g of ammonium bifluoride, 25-28 g of ammonium chloride, 2-3 g of copper chloride, 1-2 g of polyethylene glycol, 0.5-0.7 g of sodium gluconate, 6-7 g of boric acid, 5-6 g of propylene glycol, and 1-2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0015] More optimally, the working conditions of the anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5-10 min.
[0016] More optimally, in step 1, the concentration of dilute sulfuric acid is 10-12 wt %.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] (1) The present invention firstly uses a roughening liquid to roughen the cleaned aluminum alloy, thereby increasing the roughness of the aluminum alloy, thereby increasing the bonding force between the oxide film layer and the surface of the aluminum alloy. The present invention also adds γ-(2,3-epoxypropoxy)propyltrimethoxysilane to the roughening liquid, so that the surface of the aluminum alloy after the roughening process has epoxy groups, and the epoxy groups can react with the amino groups on the silicon dioxide-POSS complex, so that the corrosion-resistant oxide film is firmly attached to the surface of the aluminum alloy, thereby improving the corrosion resistance of the aluminum alloy.
[0019] (2) The present invention further performs anodizing on the aluminum alloy after the roughening process. Titanium dioxide-silicon dioxide composite sol is added to the electrolyte used for anodizing. The addition of titanium dioxide increases the density of the film, and the addition of silicon dioxide further enhances the corrosion resistance of the film, making the film layer smooth, flat, dense and uniform, with good hydrophobicity, and the film layer is tightly bonded to the aluminum alloy, thereby enhancing the corrosion resistance of the aluminum alloy.
[0020] (3) The present invention also adds a silicon dioxide-POSS composite to the electrolyte. The silicon dioxide is a multi-shell silicon dioxide particle, and the specific surface area of the silicon dioxide is larger, so that the silicon dioxide can be composited with more amino POSS; the silicon dioxide and POSS are composited together, and the high content of silicon in the POSS helps to improve the hydrophobicity of the substance, reduce the contact between the corrosive medium and the surface of the aluminum alloy, and further improve the corrosion resistance of the aluminum alloy. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1: A surface treatment method of an aluminum alloy comprises the following steps:
[0023] Step 1: Preparation of titanium dioxide-silicon dioxide composite sol:
[0024] Take 5.8g of ethyl orthosilicate, 31g of methanol, 1g of hydrochloric acid, and 1mL of deionized water, stir at 27°C for 1.5h to obtain a silica sol; take 4.5g of benzoylacetone and 31g of methanol, stir at 27°C for 35min to obtain a benzoylacetone solution, add 9.5g of tetrabutyl titanate and 4g of acrylic acid, and continue stirring for 2.5h to obtain a titanium dioxide sol; take 5g of silica sol and 5g of titanium dioxide sol, stir evenly, let stand and age for 24h to obtain a titanium dioxide-silicon dioxide composite sol;
[0025] Step 2: Preparation of silicon dioxide-POSS composite, comprising the following steps:
[0026] S1: Preparation of amino-modified POSS:
[0027] Take 5 mL of acetonitrile, 1 mL of tetraethylammonium hydroxide, 20 mL of propanol, and 50 mL of deionized water, stir evenly, add 100 g of γ-aminopropyltriethoxysilane dropwise, stir for 18 min, heat to 60 ° C, stir for 24 h, cool to 27 ° C, then add it to tetrahydrofuran at 0 ° C, precipitate, filter, and dry to obtain amino POSS;
[0028] S2: Preparation of multi-shell silica particles:
[0029] Take 86 mL of propanol and 1 mL of deionized water, stir evenly, add 2 mL of 0.2 mol / L sodium hydroxide aqueous solution, add 5 mL of tetraethyl orthosilicate at 27°C, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution again, stir for 3 h, centrifuge, wash, and dry to obtain multi-shell silica particles;
[0030] S3: Preparation of silica-POSS composite:
[0031] Take 0.1 g of amino-modified POSS, 1 g of multi-shell silica particles, and 200 mL of toluene, stir evenly, add 60 mL of Tris buffer with a pH value of 7.5, react at 80°C for 6.5 h, cool, remove the supernatant, centrifuge, precipitate, and dry to obtain a silica-POSS complex;
[0032] Step 3:
[0033] The aluminum alloy was pickled with dilute sulfuric acid having a concentration of 10 wt % for 3 seconds, washed with water, dried, and then roughened with a roughening solution for 17 minutes at a temperature of 61° C. After washing and drying, anodization was performed to obtain the treated aluminum alloy;
[0034] The roughening solution is: 1000 mL of deionized water as a solvent, wherein 123 g of ammonium bifluoride, 26 g of ammonium chloride, 2.5 g of copper chloride, 1.5 g of polyethylene glycol, 0.6 g of sodium gluconate, 6.5 g of boric acid, 5.5 g of glycerol, and 1.5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0035] The working conditions of anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5 min; the electrolyte used for anodization is: 100 mL of deionized water as a solvent, including 0.1 g of silica-POSS composite, 1.2 g of titanium dioxide-silicon dioxide composite sol, 1.3 g of sulfuric acid, and 5.5 g of disodium ethylenediaminetetraacetate.
[0036] Embodiment 2: A surface treatment method of an aluminum alloy comprises the following steps:
[0037] Step 1: Preparation of titanium dioxide-silicon dioxide composite sol:
[0038] Take 5.8g of ethyl orthosilicate, 31g of methanol, 1g of hydrochloric acid, and 1mL of deionized water, stir at 25°C for 1h to obtain a silica sol; take 4.5g of benzoylacetone and 31g of methanol, stir at 25°C for 30min to obtain a benzoylacetone solution, add 9.5g of tetrabutyl titanate and 4g of acrylic acid, and continue stirring for 2h to obtain a titanium dioxide sol; take 5g of silica sol and 5g of titanium dioxide sol, stir evenly, let stand and age for 22h to obtain a titanium dioxide-silicon dioxide composite sol;
[0039] Step 2: Preparation of silicon dioxide-POSS composite, comprising the following steps:
[0040] S1: Preparation of amino-modified POSS:
[0041] Take 5 mL of acetonitrile, 1 mL of tetraethylammonium hydroxide, 20 mL of propanol, and 50 mL of deionized water, stir evenly, add 100 g of γ-aminopropyltriethoxysilane dropwise, stir for 15 min, heat to 55 ° C, stir for 22 h, cool to 25 ° C, then add it to tetrahydrofuran at 0 ° C, precipitate, filter, and dry to obtain amino POSS;
[0042] S2: Preparation of multi-shell silica particles:
[0043] Take 86 mL of propanol and 1 mL of deionized water, stir evenly, add 2 mL of 0.2 mol / L sodium hydroxide aqueous solution, add 5 mL of tetraethyl orthosilicate at 25°C, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution again, stir for 3 h, centrifuge, wash, and dry to obtain multi-shell silica particles;
[0044] S3: Preparation of silica-POSS composite:
[0045] Take 0.1 g of amino-modified POSS, 1 g of multi-shell silica particles, and 200 mL of toluene, stir evenly, add 60 mL of Tris buffer with a pH value of 7.5, react at 80°C for 6 h, cool, remove the supernatant, centrifuge, precipitate, and dry to obtain a silica-POSS complex;
[0046] Step 3:
[0047] The aluminum alloy was pickled with dilute sulfuric acid having a concentration of 10 wt % for 3 seconds, washed with water, dried, and then roughened with a roughening solution for 15 minutes at a temperature of 60° C. After washing and drying, anodized to obtain the treated aluminum alloy;
[0048] The roughening solution is: 1000 mL of deionized water as a solvent, wherein 120 g of ammonium bifluoride, 25 g of ammonium chloride, 2 g of copper chloride, 1 g of polyethylene glycol, 0.5 g of sodium gluconate, 6 g of boric acid, 5 g of glycerol, and 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0049] The working conditions of anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5 min; the electrolyte used for anodization is: 100 mL of deionized water as a solvent, including 0.1 g of silica-POSS composite, 1 g of titanium dioxide-silicon dioxide composite sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate.
[0050] Embodiment 3: A surface treatment method of an aluminum alloy comprises the following steps:
[0051] Step 1: Preparation of titanium dioxide-silicon dioxide composite sol:
[0052] Take 5.8g of ethyl orthosilicate, 31g of methanol, 1g of hydrochloric acid, and 1mL of deionized water, stir at 30°C for 2h to obtain a silica sol; take 4.5g of benzoylacetone and 31g of methanol, stir at 30°C for 40min to obtain a benzoylacetone solution, add 9.5g of tetrabutyl titanate and 4g of acrylic acid, and continue stirring for 3h to obtain a titanium dioxide sol; take 5g of silica sol and 5g of titanium dioxide sol, stir evenly, let stand and age for 26h to obtain a titanium dioxide-silicon dioxide composite sol;
[0053] Step 2: Preparation of silicon dioxide-POSS composite, comprising the following steps:
[0054] S1: Preparation of amino-modified POSS:
[0055] Take 5 mL of acetonitrile, 1 mL of tetraethylammonium hydroxide, 20 mL of propanol, and 50 mL of deionized water, stir evenly, add 100 g of γ-aminopropyltriethoxysilane dropwise, stir for 20 min, heat to 65 ° C, stir for 26 h, cool to 30 ° C, then add it to tetrahydrofuran at 0 ° C, precipitate, filter, and dry to obtain amino POSS;
[0056] S2: Preparation of multi-shell silica particles:
[0057] Take 86 mL of propanol and 1 mL of deionized water, stir evenly, add 2 mL of 0.2 mol / L sodium hydroxide aqueous solution, add 5 mL of tetraethyl orthosilicate at 30°C, stir for 3 h at 30°C, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution again, stir for 3 h, centrifuge, wash, and dry to obtain multi-shell silica particles;
[0058] S3: Preparation of silica-POSS composite:
[0059] Take 0.1 g of amino-modified POSS, 1 g of multi-shell silica particles, and 200 mL of toluene, stir evenly, add 60 mL of Tris buffer with a pH value of 7.5, react at 85°C for 7 h, cool, remove the supernatant, centrifuge, precipitate, and dry to obtain a silica-POSS complex;
[0060] Step 3:
[0061] The aluminum alloy was pickled with dilute sulfuric acid having a concentration of 10 wt % for 4 seconds, washed with water, dried, and then roughened with a roughening solution for 20 minutes at a temperature of 62° C. After washing and drying, anodization was performed to obtain the treated aluminum alloy;
[0062] The roughening solution is: 1000 mL of deionized water as a solvent, wherein 125 g of ammonium bifluoride, 28 g of ammonium chloride, 3 g of copper chloride, 2 g of polyethylene glycol, 0.7 g of sodium gluconate, 7 g of boric acid, 6 g of glycerol, and 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0063] The working conditions of anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 10 min; the electrolyte used for anodization is: 100 mL of deionized water as a solvent, including 0.15 g of silica-POSS composite, 1.3 g of titanium dioxide-silicon dioxide composite sol, 1.5 g of sulfuric acid, and 6 g of disodium ethylenediaminetetraacetic acid.
[0064] Comparative Example 1: γ-(2,3-epoxypropoxy)propyltrimethoxysilane was not added to the roughening solution, and the rest was the same as Example 1:
[0065] Step 1: Preparation of titanium dioxide-silicon dioxide composite sol:
[0066] Take 5.8g of ethyl orthosilicate, 31g of methanol, 1g of hydrochloric acid, and 1mL of deionized water, stir at 27°C for 1.5h to obtain a silica sol; take 4.5g of benzoylacetone and 31g of methanol, stir at 27°C for 35min to obtain a benzoylacetone solution, add 9.5g of tetrabutyl titanate and 4g of acrylic acid, and continue stirring for 2.5h to obtain a titanium dioxide sol; take 5g of silica sol and 5g of titanium dioxide sol, stir evenly, let stand and age for 24h to obtain a titanium dioxide-silicon dioxide composite sol;
[0067] Step 2: Preparation of silicon dioxide-POSS composite, comprising the following steps:
[0068] S1: Preparation of amino-modified POSS:
[0069] Take 5 mL of acetonitrile, 1 mL of tetraethylammonium hydroxide, 20 mL of propanol, and 50 mL of deionized water, stir evenly, add 100 g of γ-aminopropyltriethoxysilane dropwise, stir for 18 min, heat to 60 ° C, stir for 24 h, cool to 27 ° C, then add it to tetrahydrofuran at 0 ° C, precipitate, filter, and dry to obtain amino POSS;
[0070] S2: Preparation of multi-shell silica particles:
[0071] Take 86 mL of propanol and 1 mL of deionized water, stir evenly, add 2 mL of 0.2 mol / L sodium hydroxide aqueous solution, add 5 mL of tetraethyl orthosilicate at 27°C, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution again, stir for 3 h, centrifuge, wash, and dry to obtain multi-shell silica particles;
[0072] S3: Preparation of silica-POSS composite:
[0073] Take 0.1 g of amino-modified POSS, 1 g of multi-shell silica particles, and 200 mL of toluene, stir evenly, add 60 mL of Tris buffer with a pH value of 7.5, react at 80°C for 6.5 h, cool, remove the supernatant, centrifuge, precipitate, and dry to obtain a silica-POSS complex;
[0074] Step 3:
[0075] The aluminum alloy was pickled with dilute sulfuric acid having a concentration of 10 wt % for 3 seconds, washed with water, dried, and then roughened with a roughening solution for 17 minutes at a temperature of 61° C. After washing and drying, anodization was performed to obtain the treated aluminum alloy;
[0076] The roughening solution is: 1000 mL of deionized water as solvent, including 123 g of ammonium bifluoride, 26 g of ammonium chloride, 2.5 g of copper chloride, 1.5 g of polyethylene glycol, 0.6 g of sodium gluconate, 6.5 g of boric acid, and 5.5 g of glycerol;
[0077] The working conditions of anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5 min; the electrolyte used for anodization is: 100 mL of deionized water as a solvent, including 0.1 g of silica-POSS composite, 1.2 g of titanium dioxide-silicon dioxide composite sol, 1.3 g of sulfuric acid, and 5.5 g of disodium ethylenediaminetetraacetate.
[0078] Comparative Example 2: No silica composite sol was added, and the rest was the same as Example 1:
[0079] Step 1: Preparation of titanium dioxide sol:
[0080] Take 4.5g of benzoylacetone and 31g of methanol, stir at 25-30°C for 30-40min to obtain a benzoylacetone solution, add 9.5g of tetrabutyl titanate and 4g of acrylic acid, continue stirring for 2-3h to obtain a titanium dioxide sol;
[0081] Step 2: Preparation of silicon dioxide-POSS composite, comprising the following steps:
[0082] S1: Preparation of amino-modified POSS:
[0083] Take 5 mL of acetonitrile, 1 mL of tetraethylammonium hydroxide, 20 mL of propanol, and 50 mL of deionized water, stir evenly, add 100 g of γ-aminopropyltriethoxysilane dropwise, stir for 18 min, heat to 60 ° C, stir for 24 h, cool to 27 ° C, then add it to tetrahydrofuran at 0 ° C, precipitate, filter, and dry to obtain amino POSS;
[0084] S2: Preparation of multi-shell silica particles:
[0085] Take 86 mL of propanol and 1 mL of deionized water, stir evenly, add 2 mL of 0.2 mol / L sodium hydroxide aqueous solution, add 5 mL of tetraethyl orthosilicate at 27°C, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution again, stir for 3 h, centrifuge, wash, and dry to obtain multi-shell silica particles;
[0086] S3: Preparation of silica-POSS composite:
[0087] Take 0.1 g of amino-modified POSS, 1 g of multi-shell silica particles, and 200 mL of toluene, stir evenly, add 60 mL of Tris buffer with a pH value of 7.5, react at 80°C for 6.5 h, cool, remove the supernatant, centrifuge, precipitate, and dry to obtain a silica-POSS complex;
[0088] Step 3:
[0089] The aluminum alloy was pickled with dilute sulfuric acid having a concentration of 10 wt % for 3 seconds, washed with water, dried, and then roughened with a roughening solution for 17 minutes at a temperature of 61° C. After washing and drying, anodization was performed to obtain the treated aluminum alloy;
[0090] The roughening solution is: 1000 mL of deionized water as a solvent, wherein 123 g of ammonium bifluoride, 26 g of ammonium chloride, 2.5 g of copper chloride, 1.5 g of polyethylene glycol, 0.6 g of sodium gluconate, 6.5 g of boric acid, 5.5 g of glycerol, and 1.5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0091] The working conditions of anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5 min; the electrolyte used for anodization is: 100 mL of deionized water as a solvent, including 0.1 g of silica-POSS composite, 1.2 g of titanium dioxide sol, 1.3 g of sulfuric acid, and 5.5 g of disodium ethylenediaminetetraacetate.
[0092] Comparative Example 3: No amino POSS was added, and the rest was the same as Example 1:
[0093] Step 1: Preparation of titanium dioxide-silicon dioxide composite sol:
[0094] Take 5.8g of ethyl orthosilicate, 31g of methanol, 1g of hydrochloric acid, and 1mL of deionized water, stir at 27°C for 1.5h to obtain a silica sol; take 4.5g of benzoylacetone and 31g of methanol, stir at 27°C for 35min to obtain a benzoylacetone solution, add 9.5g of tetrabutyl titanate and 4g of acrylic acid, and continue stirring for 2.5h to obtain a titanium dioxide sol; take 5g of silica sol and 5g of titanium dioxide sol, stir evenly, let stand and age for 24h to obtain a titanium dioxide-silicon dioxide composite sol;
[0095] Step 2: Preparation of multi-shell silica particles:
[0096] Take 86 mL of propanol and 1 mL of deionized water, stir evenly, add 2 mL of 0.2 mol / L sodium hydroxide aqueous solution, add 5 mL of tetraethyl orthosilicate at 27°C, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 2 mL of 0.3 mol / L sodium hydroxide aqueous solution again, stir for 3 h, centrifuge, wash, and dry to obtain multi-shell silica particles;
[0097] Step 3:
[0098] The aluminum alloy was pickled with dilute sulfuric acid having a concentration of 10 wt % for 3 seconds, washed with water, dried, and then roughened with a roughening solution for 17 minutes at a temperature of 61° C. After washing and drying, anodization was performed to obtain the treated aluminum alloy;
[0099] The roughening solution is: 1000 mL of deionized water as a solvent, wherein 123 g of ammonium bifluoride, 26 g of ammonium chloride, 2.5 g of copper chloride, 1.5 g of polyethylene glycol, 0.6 g of sodium gluconate, 6.5 g of boric acid, 5.5 g of glycerol, and 1.5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0100] The working conditions of anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5 min; the electrolyte used for anodization is: 100 mL of deionized water as a solvent, including 0.1 g of silica-POSS composite, 1.2 g of titanium dioxide-silicon dioxide composite sol, 1.3 g of sulfuric acid, and 5.5 g of disodium ethylenediaminetetraacetate.
[0101] experiment:
[0102] The treated aluminum alloys prepared in Examples 1-3 and Comparative Examples 1-3 were used for performance testing. The aluminum alloy was 7A04-T6 aluminum alloy, and the sample size was 150 mm×100 mm×1 mm. The tensile strength of the aluminum alloy was tested. The aluminum alloy was then placed in a salt spray chamber at a temperature of 35° C. for 60 days, and a sodium chloride aqueous solution with a concentration of 60 g / L was used to test the salt spray resistance of the aluminum alloy. The water contact angle on the surface of the aluminum alloy was tested, and the data obtained are shown in the following table:
[0103]
[0104]
[0105] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is not added to the roughening solution, rust spots appear on the surface of the aluminum alloy, and the corrosion resistance of the aluminum alloy decreases. No rust spots appear on the aluminum alloy of Examples 1-3, and the corrosion resistance is good. In Examples 1-3, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to the roughening solution, so that the surface of the aluminum alloy after the roughening process is provided with epoxy groups, and the epoxy groups can react with the amino groups on the silica-POSS complex, so that the corrosion-resistant oxide film is firmly attached to the surface of the aluminum alloy, thereby improving the corrosion resistance of the aluminum alloy. In Comparative Example 2, silica sol is not added, the compactness of the oxide film deteriorates, and the corrosion resistance of the aluminum alloy decreases. In Examples 1-3, silica sol is added, so that the film layer is smooth, flat, dense and uniform, has good hydrophobicity, and the film layer is tightly bonded to the aluminum alloy, thereby enhancing the corrosion resistance of the aluminum alloy. In comparative example 3, no amino POSS is added, the corrosion resistance of the aluminum alloy decreases, and the hydrophobicity of the aluminum alloy surface deteriorates. In examples 1-3, silicon dioxide is compounded with POSS, and the high silicon content in POSS helps to improve the hydrophobicity of the material, reduce the contact between the corrosive medium and the aluminum alloy surface, and further improve the corrosion resistance of the aluminum alloy.
[0106] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A surface treatment method for aluminum alloy, characterized in that: The following steps are involved: Step 1: Take the aluminum alloy, pickle it with dilute sulfuric acid for 3-4 seconds, wash it with water, and dry it; Step 2: roughening the cleaned aluminum alloy with a roughening liquid for 15-20 minutes at a temperature of 60-62° C., cleaning, drying, and then anodizing to obtain a treated aluminum alloy; The electrolyte used for anodization is: 100 mL of deionized water as solvent, wherein: 0.1-0.15 g of silica-POSS composite, 1-1.3 g of titanium dioxide-silicon dioxide composite sol, 1.2-1.5 g of sulfuric acid, and 5-6 g of disodium ethylenediaminetetraacetate; The preparation method of the silica-POSS complex is as follows: taking amino POSS, multi-shell silica particles, and toluene, stirring evenly, adding Tris buffer with a pH value of 7.5, reacting at 80-85° C. for 6-7 hours, cooling, removing the supernatant, centrifuging, precipitating, and drying to obtain the silica-POSS complex; The roughening solution is: 1000 mL of deionized water as a solvent, wherein the solvent includes 120-125 g of ammonium bifluoride, 25-28 g of ammonium chloride, 2-3 g of copper chloride, 1-2 g of polyethylene glycol, 0.5-0.7 g of sodium gluconate, 6-7 g of boric acid, 5-6 g of propylene glycol, and 1-2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
2. The surface treatment method of an aluminum alloy according to claim 1, characterized in that: The preparation method of the multi-shell silica particles is as follows: take propanol and deionized water, stir evenly, add sodium hydroxide aqueous solution, add tetraethyl orthosilicate at 25-30° C., stir for 3-4 hours at 25-30° C., add sodium hydroxide aqueous solution, stir for 3-4 hours, add sodium hydroxide aqueous solution again, stir for 3-4 hours, centrifuge, wash, and dry to obtain multi-shell silica particles.
3. The surface treatment method of an aluminum alloy according to claim 1, characterized in that: The preparation method of the amino POSS is as follows: acetonitrile, tetraethylammonium hydroxide, propanol and deionized water are taken, stirred evenly, γ-aminopropyltriethoxysilane is added dropwise and stirred for 15-20 minutes, the temperature is raised to 55-65° C., stirred for 22-26 hours, cooled to 25-30° C., and then added to tetrahydrofuran at 0° C., precipitated, filtered and dried to obtain the amino POSS.
4. The surface treatment method of an aluminum alloy according to claim 1, characterized in that: The preparation method of the titanium dioxide-silicon dioxide composite sol is as follows: taking ethyl orthosilicate, methanol, hydrochloric acid and deionized water, stirring for 1-2 hours at 25-30° C. to obtain a silicon dioxide sol; taking benzoyl acetone and methanol, stirring for 30-40 minutes at 25-30° C. to obtain a benzoyl acetone solution, adding tetrabutyl titanate and acrylic acid, and continuing to stir for 2-3 hours to obtain a titanium dioxide sol; taking the silicon dioxide sol and the titanium dioxide sol, stirring evenly, standing and aging for 22-26 hours to obtain a titanium dioxide-silicon dioxide composite sol.
5. The surface treatment method of an aluminum alloy according to claim 1, characterized in that: The working conditions of the anodization are: an AC power supply of 1 kW, a constant current of 0.3 A, a frequency of 100 Hz, and a time of 5-10 min.
6. The surface treatment method of an aluminum alloy according to claim 1, characterized in that: In step 1, the concentration of dilute sulfuric acid is 10-12 wt %.
Citation Information
Patent Citations
Ordinary temperature curing high-hardness organic-inorganic hybrid coating as well as preparation and use method thereof
CN103965778A
Method for preparing multi-shell hollow silica particles
CN107673361A